KUALITAS PELAYANAN PUBLIK DI DESA SIWONGI KECAMATAN KULAWI KABUPATEN SIGI - Budi, Budi (Katalogis, 2021)
This study aims to find out how the quality of public services in Siwongi Village, Kulawi Subdistrict, Sigi Regency, is more specifically regarding Population Administration services. The basis of the research used is qualitative, while the type of research used is descriptive. The informants used in this study were determined purposively, with a total of 7 (seven) informants. Data collection techniques used were observation, interviews and documentation. This study uses the Parasuraman theory where there are 5 (five) dimensions to measure service quality, namely Tangibles, Realiability, Responsiveenes, Asurance, and Empathy. The results of this study indicate that the Quality of Public Services at Siwongi Village office is from dimension (i). tangibles (direct evidence) are in the bad category; (ii). seen from the dimensions of reliability (reliability) are in the less good category; (iii) Responsiveness (responsiveness) is in the good category; (iv) seen from the dimension of insurance (guarantee) in the category of poor (v) seen from the dimension of Empathy in the good category; Based on the results of the study it can be concluded that from the 5 (five) dimensions studied the category is not good, so it needs to be improved, it is expected that the Siwongi Village Government will make continuous improvements to the 5 service dimensions, so that in the future the service will be at Siwongi District Sigi, can satisfy the community.